Fluid-rock reactions in the carbonatites of the Grønnedal-Íka alkaline complex, South Greenland - Ranta, Eemu (Helsingfors universitet, 2017)
Out of all igneous rocks, carbonatites are perhaps the ones most sensitive to changing chemical environments and P-T conditions. As a result, their primary chemical and textural characteristics are more often than not altered by secondary processes. Discerning between the two is essential in order to make correct petrogenetic inferences from textural and chemical data. In this study, the 1.3 Ga siderite carbonatite of the Grønnedal-IÌ ka alkaline complex of South Greenland is used as a natural laboratory to identify mineral chemical and textural fingerprints of hydrothermal alteration in iron-rich carbonatites, with a second aim of describing the paragenesis of a high-grade magnetite mineralization in the locality. Trace element chemistry of magnetite, calcite, siderite and ankerite-dolomite is analyzed in situ by electron-probe microanalysis (EPMA) and laser ablation inductively coupled mass spectrometry (LA- ICP-MS). Magnetite is shown to be a product of oxidation of siderite and is exclusively of hydrothermal origin, characterized by low Ti (1-12000 ppm) and V (1-200 ppm) concentrations. High Nb/Ta (up to 1000) and Zr/Hf (up to 300) ratios in magnetite suggest formation mediated by fluorine-rich fluids. Hydrothermally reworked siderite is enriched in Mn and light rare earth elements (LREEs) and has a depleted Y/Ho ratio. In contrast, hydrothermally reworked calcite is enriched in Y/Ho and depleted in LREEs. A secondary mineral assemblage of apatite, strontianite, barite, REE-fluorocarbonates and ankerite-dolomite is associated with the alteration, which increases toward the contact to a 55 m wide basaltic dike that cuts the carbonatite. Unusual mineral compositions are found close to the dike contact, including magnetite with up to 1 wt.% Nb and calcite with 1 wt.% REEs, both the highest reported values in the literature. Together, the data point to the dike intrusion as a heat source of a hydrothermal convection cell, driving hot F and CO2 rich fluids that mobilized P, Sr, Ba, Mn, LREE, Nb and Ta and reacted ...